Persepsi Anggota Kelompok Tani Urban terhadap Profesi Petani di Era Digital - Gisky Andria Putra; Nike Widuri; Midiansyah Effendi (MAN 4 Kota Pekanbaru, 2026)
This study aims to describe the perceptions of farmer group members toward the farming profession in the digital era. The research was conducted in Samarinda City, East Kalimantan Province. The sampling technique employed was purposive sampling, involving a total of 12 research informants. The obtained data were analyzed using the Miles and Huberman analysis technique, which comprises four stages: data collection, data reduction, data display, and conclusion drawing and verification. This study reveals that the perceptions of farmer group members toward the farming profession are dualistic, on one hand, there is a strong collective awareness of the strategic role of agriculture as a food provider, while on the other hand, negative social stigmas from the general public which identify the farming profession with backwardness and poverty still persist. Furthermore, the farmers' motivation to remain in the agricultural sector is sustained by three main pillars: economic factors in the form of promising agricultural yields, experience and deeply rooted work identity, and social factors through the existence of farmer groups that provide solidarity, psychological support, and collective social capital.